Validity and reliability of patient-reported outcomes measurement information system instruments in osteoarthritis. - Broderick, Joan E; Schneider, Stefan; Junghaenel, Doerte U; Schwartz, Joseph E; Stone, Arthur A (Arthritis Care & Research, 2013)
Objective: Evaluation of known-group validity, ecological validity, and test-retest reliability of 4 domain instruments from the Patient-Reported Outcomes Measurement Information System (PROMIS) in osteoarthritis (OA) patients.Methods: We recruited an OA sample and a comparison general population (GP) sample through an internet survey panel. Pain intensity, pain interference, physical functioning, and fatigue were assessed for 4 consecutive weeks with PROMIS short forms on a daily basis and compared with same-domain Computer Adaptive Testing (CAT) instruments that use a 7-day recall. Known-group validity (comparison of OA and GP), ecological validity (comparison of aggregated daily measures with CAT instruments), and test-retest reliability were evaluated.Results: The recruited samples matched the demographic characteristics (age, sex, race, and ethnicity) of the US sample for arthritis and the 2009 Census for the GP. Compliance with repeated measurements was excellent at >95%. Known-group validity for CATs was demonstrated with large effect sizes (pain intensity 1.42, pain interference 1.25, and fatigue 0.85). Ecological validity was also established through high correlations between aggregated daily measures and weekly CATs (≥0.86). Test-retest validity (7-day) was very good (≥0.80).Conclusion: PROMIS CAT instruments demonstrated known-group and ecological validity in a comparison of OA patients with a GP sample. Adequate test-retest reliability was also observed. These data provide encouraging initial data on the utility of these PROMIS instruments for clinical and research outcomes in OA patients.